Entrepreneurial Networking of Small Businesses in Latin-America: The Case of Villa el Salvador in Peru - Pérez Centeno, Víctor (2014)
Descargue el texto completo en el repositorio institucional de la University of Jyväskylä: http://urn.fi/URN:ISBN:978-951-39-5626-4